2019
DOI: 10.1111/tri.13530
|View full text |Cite
|
Sign up to set email alerts
|

Rapid discontinuation of prednisone in kidney transplant recipients from at‐risk subgroups: an OPTN/SRTR analysis

Abstract: Summary Although rapid discontinuation of prednisone (RDP) after kidney transplantation has been successful in low‐risk recipients, there is concern about RDP use in recipients at increased risk for rejection or recurrent disease. Using SRTR, we compared outcomes for RDP versus maintenance prednisone‐treated recipients for all adult 1st and 2nd transplants (n = 169 479) and the following 1st transplant subgroups: African American (AA); highly sensitized; those with a potentially recurrent disease; and pediatri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…Although, firstly steroid sparing immunosuppressive regimens were used for low immunologic risk patients, an analysis of 169479 renal transplant patients using SRTR exhibited that rapid discontinuation of steroids can be used in all adult and pediatric first kidney transplant recipients from deceased or living donor and even in second kidney transplant recipients from living donor or patients at risk for rejection or recurrence of underlying diseases, without decreasing patients' or graft survivals. Only in adult patients with second kidney transplantation from deceased donor, rapid steroid withdrawal was associated with worse graft survival [9] . Another systematic review and meta-analysis consisting 7 cohort studies that included even high-risk kidney transplant patients such as re-transplant patients, African-American ethnicity or recipients with panel reactive antibody (PRA) of 20% or more found that acute rejection episodes and graft loss were comparable between patients maintained on steroids compared with steroid withdrawal or avoidance group.…”
Section: Gcs As Induction and Maintenance Immunosuppressive Therapymentioning
confidence: 97%
See 1 more Smart Citation
“…Although, firstly steroid sparing immunosuppressive regimens were used for low immunologic risk patients, an analysis of 169479 renal transplant patients using SRTR exhibited that rapid discontinuation of steroids can be used in all adult and pediatric first kidney transplant recipients from deceased or living donor and even in second kidney transplant recipients from living donor or patients at risk for rejection or recurrence of underlying diseases, without decreasing patients' or graft survivals. Only in adult patients with second kidney transplantation from deceased donor, rapid steroid withdrawal was associated with worse graft survival [9] . Another systematic review and meta-analysis consisting 7 cohort studies that included even high-risk kidney transplant patients such as re-transplant patients, African-American ethnicity or recipients with panel reactive antibody (PRA) of 20% or more found that acute rejection episodes and graft loss were comparable between patients maintained on steroids compared with steroid withdrawal or avoidance group.…”
Section: Gcs As Induction and Maintenance Immunosuppressive Therapymentioning
confidence: 97%
“…As maintenance immunosuppressive therapy, some centers are shifting toward steroid sparing maintenance immunosuppressive regimens by different steroid withdrawal or avoidance protocols [1][2][3] . Steroid sparing means rapid, early, or late steroid discontinuation (within one week to several months after transplantation), while steroid avoidance refers to avoiding steroid use in regimens with or without initial high corticosteroid induction therapy [3,[9][10][11][12] . Although old studies on steroid sparing regimens that usually were GC minimization or discontinuation after 3 months of transplant surgery showed higher rates of acute rejection and graft loss, in those studies immunosuppressive regimens contained cyclosporine as a CNI [13] .…”
Section: Gcs As Induction and Maintenance Immunosuppressive Therapymentioning
confidence: 99%
“…As maintenance immunosuppressive therapy, some centers are shifting toward steroid sparing maintenance immunosuppressive regimens by different steroid withdrawal or avoidance protocols[ 1 - 3 ]. Steroid sparing means rapid, early, or late steroid discontinuation (within 1 wk to several months after transplantation), while steroid avoidance refers to avoiding steroid use in regimens with or without initial high corticosteroid induction therapy[ 3 , 9 - 12 ]. Although old studies on steroid sparing regimens (GC minimization or discontinuation after 3 mo of transplant surgery) showed higher rates of acute rejection and graft loss, in those studies immunosuppressive regimens contained cyclosporine as a CNI[ 13 ].…”
Section: Transplant Recipientsmentioning
confidence: 99%
“…Although old studies on steroid sparing regimens (GC minimization or discontinuation after 3 mo of transplant surgery) showed higher rates of acute rejection and graft loss, in those studies immunosuppressive regimens contained cyclosporine as a CNI[ 13 ]. Nowadays, induction therapies with thymoglobulin or IL2 receptor antagonists and new maintenance immunosuppressive regimens, such as tacrolimus instead of cyclosporine as CNI or mTOR inhibitors, in combination with low doses of CNIs and/or mycophenolate, provided the opportunity for successful steroid-sparing immunosuppression regimens[ 1 , 9 - 11 , 14 , 15 ]. Although, steroid sparing immunosuppressive regimens were used for low immunological risk patients, an analysis of 169479 renal transplant patients using the Scientific Registry of Transplant Recipients found that rapid discontinuation of steroids can be used in all adult and pediatric first kidney transplant recipients from either a deceased or living donor and in second kidney transplant recipients from a living donor or patients at risk for rejection or recurrence of underlying diseases without decreasing patients’ or graft survival rates.…”
Section: Transplant Recipientsmentioning
confidence: 99%
See 1 more Smart Citation